Clinical performance of reverse transcription loop mediated isothermal amplification COVID-19 assay on gold- nanoparticle-modified screen-printed Carbon Electrode using differential pulse voltammetry - Zulhairee, Munirah; Mohd Zain, Rozainanee; Che Mohamad Nor, Adibah; Jafar, Nur Fadhilah; Md Noh, Mohd Fairulnizal; Ahmad Noorden, Mohd Shihabuddin; Nordin, Anis Nurashikin; Ab Rahim, Rosminazuin; Gunawan, Teddy Surya; Chin, Lim Ying; Mohd, Yusairie; Azman, Nur Asyiqin; et al. (MYU K.K., 2023)
The World Health Organization (WHO) has recommended real-time reverse transcription polymerase chain reaction (RT-PCR) as the gold standard for coronavirus disease detection. In this study, we aim to validate the clinical performance of reverse transcription loop-mediated isothermal amplification (RT-LAMP) assay on gold-nanoparticle-modified screen-printed carbon electrode (AuNP/SPCE) using differential pulse voltammetry (DPV) and to compare it with real-time RT-PCR. The shape of the electrodeposited AuNP on SPCE was quasi-spherical with a size of ±500 nm. The developed RT-LAMP primer was designed from the GenBank database using the NCBI Multiple Alignment tools and Jalview software. Nasopharyngeal clinical samples were obtained from suspected COVID-19 patients (n = 148). The RT-LAMP products were dropped on the modified AuNP/SPCE under DPV setting, which resulted in current change (∆I) responses. The positive and negative samples produced significantly different ∆I signals with a p-value <0.0001 at a 95% confidence interval using Student’s t-test. The RT-LAMP assay using Au/SPCE exhibited a 30 s response time per analysis. The clinical sensitivity and specificity obtained were 79.7% and 85.1%, respectively, with a detection limit of 0.4 copies µl−1. Hence, this proposed method is suitable for COVID-19 RNA detection in resource-limited settings.